Optimasi Pendistribusian Air Mineral menggunakan Algoritma Genetika - Arsti Syadzwina Fauziah; Imam Cholissodin; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Distribution is one of the marketing activities carried out with the aim of distributing products from producers to consumers. This distribution is very important in marketing activities, if there is no distribution activity then the goods will not reach consumers from less affordable areas. Mineral water products almost dominate the beverage industry market and with population growth it is possible that the need for mineral water will continue to increase. At the point when the interest for mineral water expands, the job of distribution turns out to be important. In this distribution interaction, a method is needed that can handle the problems, this research was carried out using the Genetic Algorithm method in finding the optimization value contained in the Traveling Salesman Problem (TSP) to find the optimal total distance value in this distribution activity. Based on this research, the parameters are the cr 0.1, the mr 0.9, the popsize is 1000th population. The maximum iteration is 100th generation, the average fitnesss is 0.006438, and the total distance generated is more optimal than the route made by the courier of 35.3 km on the first courier, 35.8 km on the second courier and 34.9 km on the third courier.